Pembuatan Pembangkit Listrik Tenaga Sampah (PLTSA) dengan Memanfaatkan Sampah Plastik Sebagai Alat Konversi Energi - Dinda Putri Zulfira; Desi Fitriana; Nurjannah Berutu; Nurul Mayanti Fitri; Nurmasyitah Nurmasyitah (International Forum of Researchers and Lecturers, 2024)
A simple thermal waste generator is a promising solution for managing waste and generating electricity. This study aims to design and develop the tool. Through waste composition analysis, thermal design planning, prototype construction, and tool performance testing, we succeeded in creating an effective prototype. In performance testing, this tool is able to generate enough electrical power to meet daily energy needs on a small scale. Thus, this simple thermal waste power generator shows potential as an effective and environmentally friendly solution. Nevertheless, further research is needed to improve the efficiency and scalability of the tool, as well as to optimize the management of the residue from burning waste.